Parasetamol üretimi atıksuyunun anaerobik arıtılabilirliğinin incelenmesi - Gürvardar, Sedef (Fen Bilimleri Enstitüsü, 1997)
Parasetamol üretimi atıksulan yüksek organik yüke sahiptir. Bu atıksulann doğaya deşarjından önce arıtılması zorunludur. Yapılan bu çalışmada parasetamol üretimi atık suyunun anaerobik antılabilirliği incelenmiştir. İlk olarak 14500 mgO2/l KOİ değerine sahip sentetik parasetamol çözeltisinin anaerobik arıtımı sağlanmış. Bu sonuçla, parasetamol üretimi atıksuyunun arıtım çalışmalarına başlanmıştır. Seyreltilen atıksudan KOİ konsantrasyonları 17500 ve 19500 mgO2/l olan çözeltiler anaerobik arıtmaya tabi tutulmuştur. KOİ konsantrasyonu 17500 mg02/l olan çözeltide anaerobik arıtım sağlanırken, diğerinde arıtım gerçekleşmemiştir. Sabit organik yüke sahip (KOİ= 19000 mgO2/1) atıksu çözeltilerine artan konsantrasyonlarda nikel iyonu (100, 200 ve 300 mg/1) ilave edildiğinde her üç çözeltide de anaerobik arıtım sağlanmıştır. Bunlardan en iyi arıtımı sağlayan konsantrasyon (300 mg/1) seçilerek parasetamol atiğinin antılabileceği en yüksek organik yük.(2200Ö mg02/î) tesbıt edilmiştir

Recently, rapid industrialization has caused an increased environmental pollution especially the water pollution restricting the beneficial use of water resources. Water that has been used for industrial or domestic purposes may become polluted to the extent that return of the effluent into the natural water system may alter its chemical, physical or biological composition. Basic parameters in water characterization are below: 1) Physical properties a) Color b) Odor c) Solids d) Temperature e) Density f) Turbidity g) Foam h)Radioactivity 2) Chemical properties a) Chemical oxygen demand b) Total organic carbon c) Carbohydrates d) Fats, oils and grease e) Pesticides f) Phenols g) Proteins h) Surfactants 1) Nitrogen, sulfur and phosphorus j) Chlorides k) pH, alkalinity, acidity 1) Heavy metals 3) Biological properties a) Biochemical oxygen demand b) Animal, plants c) Protists (eubacteria, archaebacteria) d) Viruses It is convenient to classify waste treatment techniques into three groups, on the basis of physical, chemical, and biological operations. Treatment methods in which the application of physical forces predominate are known as physical unit operations. Screening, mixing, sedimentation, flocculation, flotation, filtration and gas transfer are typical unit operations. Treatment methods in which the removal or conversion of contaminants is brought about by addition of chemicals or by other chemical reactions are known as chemical unit processes. Precipitation, adsorption, and disinfection are the most common example in wastewater treatment. Treatment methods in which the removal of contaminants is brought about by biological activity are known as biological unit processes. Biological treatment is used primarily to remove the biodegradable organic substances in wastewater. Basically, these substances are converted into gasses that can be removed by settling. Biological treatment of industrial waste has been succesful for wastewater treatment. Biological treatment design has been divided into aerobic and anaerobic processes. The basic difference between aerobic and anaerobic oxidation is that in the aerobic system, oxygen is the ultimate hydrogen acceptor with a large release of energy, but in anaerobic systems the ultimate hydrogen acceptor may be nitrate, sulphate or an organic compound with a much lower release of energy. Biological treatment in aerobic methods includes lagooning, biological filtration and activated sludge process. Anaerobic treatment is the biological process in the absence of oxygen for the stabilization of organic matters by conversion to CEU and inorganic end products such as carbondioxide and ammonia. Anaerobic decomposition of organic wastes is a stepwise process. The anaerobic metabolism of a complex substrate, including suspended organic matter, can be regarded as a three step process: 1. Step: Hyrolysis of suspended organics of high molecular weight. 2. Step: Degradation of small organic molecules to various volatile fatty acids, ultimately acetic acid. 3. Step: Production of methane, primarily from acetic acid but also from hydrogen and carbondioxide. Anaerobic processes are specially suited to the treatment of heavily contaminated organic effluents (>5000 mg COD/1). The anaerobic digestion process is used widely for treating municipal waste sludge and is finding increasing use in treating industrial wastes which contain high concentrations of organic matters. The most significant points of this method are the production of methane gas, the minimal production of excess biological sludge, no aeration necessary (low power requirement) and heavy metal precipitation in the reactor by conversion into insoluble sulfides. The disadvantages of these processes are very sensitive to external stimulations such as changes in temperature, pH, mixing and the treated effluent is still fairly heavily polluted (about 200-300 mg O2/I COD under favourable conditions). The aim of this work was to search anaerobic treatability of paracetamol production wastewater and was to find the effect of nickel in this proceses. Pharmaceutical wastes major difficulties for proper handling and treatment. This especially true for antibiotic production by fermentation: 1) There is a number of different sources generating wastewaters. 2) A major portion of the process wastes is very strong, with high BOD and COD, high dissolved solids, varying pH, high sulfates from acidification, etc. 3) The wastewater flow pattern may exhibit irregularities and variations as the production is carried out on a batch basis and may change daily. 4) The waste composition make it almost impossible to assign reasonably reliable values for wastewater parameters, simply on the basis of production category of the plant; it is now recognized that uniformity applicable pollution profiles, relating the magnitude of pollution figures to production by means of revelant parameters, can not be defined for the entire catagory of fermentation wastes. This necessitates detailed experimental evaluation for wastewaters generated from each individual pharmaceutical plant in order to define the most appropriate treatment technology. Diffrent sources of pharmaceutical wastewater may be regrouped as below: a) wastewaters from fermentation processes b) wastewaters from extraction and purification processes c) wastewaters from recovery process d) floor and equipment washings e) laboratary wastes f) sanitary wastes g) waste cooling water Heavy metals can orginate from industrial, commerical and domestic sources. In the case of combined sewers, storm water can represent a significant source of heavy metals. They are removed by primary and secondary treatment from municipal wastewaters. A trace level of metals is required for the function of many enzymes and co-enzymes. In excessive amounts, inhibition or toxicity occurs. Heavy metal toxicity occures due to the disruption of enzyme function and structure by binding with protein molecules. Since wastewaters consist of complex organic matters and it is not possible to measure the organic content each of them individually, it is necessary to use collective parameters such as chemical oxygen demand (COD), biochemical oxygen demand (BOD) and total organic carbon (TOC), volatile fatty acids (VFA). The chemical oxygen demand is used as a measure of the oxygen equivalent of the organic matter content of a sample that is suspectable to oxidation by a strong chemical oxidant. To determine the influent characteristics, one of the most commonly used parameter is COD. In this study, anaerobic treatability of paracetamol production wastewaters was experimentally investigated. The properties of the wastewater are determined at the beginning of the study and the values are given below: COD: 84173 mg02/l pH: 2.95 Color: Light yellow Total Solids (TS)= 16000 mg/1 Volatile Suspended Solids (VSS)= 180 mg/1 S042"= 5810 mg/1 P043"= 4.54 mg/1 In the experimental study, first of all any of the leaks in the anaerobic reactor were prevented. All experiments were done in fixed temperature (37°C). In the all experiments the anaerobic reactor was fed with diluted wastewater (225 ml) and anaerobic sludge. The biogas formation in anaerobic treatment was measured with a gas measure system. Beginning of all experiments 5 mi's of samples were taken in the system, in order to determine COD, VFA, TS, TSS, TDS parameters. When the pH value was greater than 7.5 and fewer than 6.8 then pH value has regulated with the addition of NaOH and HC1 solutions. First of all, synthetic paracetamol solution were prepared in 14500 mg O2/I COD and treated anaerobically. (Paracetamol production wastewaters have diluted in two different concentrations of COD (17500 and 19500 mg O2/I). The diluted wastewater which had 17500 mg O2/I COD value, was treated anaerobically. But the other has observed inhibition). (Figure 1) 20000 ». 18000 ;. 16000 s? 14000 j g 12000 f ' 10000 8000 o U 6000 4000 2000 + 0 - ¦- KOİ-19500 t ;- a- KOİ-17500 50 100 150 200 250 300 350 Time (hour) Figure 1. COD changing at anaerobic treatment of wastewater which have 17500 and 19500 mg02/l COD The wastewaters, which have three different nickel concentrations (100, 200 and 300 mg/1) have prepared from the wastewater that contain 19000 mg02/l COD. All of them were treated anaerobically. The diluted wastewater, which had 300 mg/1 nickel ions, was the most successful treatment (Figure 2). ¦a. a, Q O U 20000 18000 16000 14000 12000 10000 8000 6000 4000 2000 0 -100mg/INi -200 mg/l Ni -300 mg/1 Ni 0 50 100 150 200 250 300 350 400 Time (hour) Figure 2. COD changing of 100, 200 ve 300 mg/1 nickel having wastewater that has 19000 mg02/l COD at anaerobic treatment. The wastewater which has 300 mg/1 Ni concentration diluted in three different concentrations of COD (22000, 27000 and 30500 mg 02/l). The diluted wastewater, which had 22000 mg 02/l COD value, was treated anaerobically. But in the other studies has observed the inhibition (Figure 3). 200 300 Time (hour) - ¦- KOİ-19000 - ¦- KOİ-30500 - a- KOl-27000 -*- KOİ-22000 400 500 Figure 3. COD changing of 300 mg/1 nickel having wastewater that have 19000, 22000, 27000 and 305000 mg02/l COD at anaerobic treatment.
Anaerobic treatment of paracetamol production wastewater
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Keywords: Anerobik arıtma; Asetaminofen; Endüstriyel atık su; Anaerobic treatment; Acetaminophen; Industrial waste water